Citizens' perspectives on healthy weight approaches in low SEP neighborhoods: a qualitative study from a systems perspective - Maud J. J. ter Bogt; Yentl Z. Te Riele; Piet G. C. Kooijman; Anita N. Heszler; Saskia van der Meer; Rob van Roon; Gerard R. M. Molleman; Maria van den Muijsenbergh; Gerdine A. J. Fransen; Kirsten E. Bevelander (BMC, 2024)
Abstract Background The physical and the social environment are important predictors of healthy weight, especially in low socioeconomic position (SEP) neighborhoods. Many Dutch municipalities have implemented a healthy weight approach (HWA). Yet, there is room for improvement. This system science study examined what influences the utilization of HWA facilities and activities, and what aspects can help to achieve a desired systems change (also called leverage point themes (LPTs)) in the HWA system as perceived by citizens living in low SEP neighborhoods. Method All research phases were performed with four citizens co-researchers. Forty-seven citizens living in low SEP neighborhoods were semi-structurally interviewed about the neighborhood HWA facilities and municipal HWA activities. A rapid coding qualitative analysis approach was applied per topic. The topics were citizens' healthy living description, personal circumstances, and satisfaction with foot and cycle paths, sports facilities, playgrounds, green spaces, museums and theaters, community centers, churches, healthcare, school, food supplies, contact with neighborhood, unfamiliar and/or unused activities, familiar and used activities, unavailable but desired (lacking) activities, and reaching citizens. Results The utilization of HWA facilities and activities was influenced by the overarching themes of social cohesion, familiarity, reaching citizens, maintenance, safety, physical accessibility, financial accessibility, social accessibility, fit with personal context, and fit with the neighborhood's specific needs. Different overarching themes stood out across different facilities and activities. LPTs indicated the overarching themes needed in combination with one another for a specific activity or facility to increase utilization. For example, the LPT regarding foot and cycle paths was "accessible, safe, and maintained foot and cycle paths". The LPTs regarding familiar and used activities were "customized activities; information provision (e.g., about possibilities to join without paying); social contact, meeting others, and everyone feels included". Conclusion Conducting inclusive qualitative research from a systems perspective among citizens living in low SEP neighborhoods has contributed valuable insights into their needs. This enables practical implementation of HWAs by providing a deeper understanding of the LPTs within the HWA system. LPTs can help HWA stakeholders to further develop current HWAs toward systems approaches. Future research could study the leverage points that may contribute to LPT implementation.